Temporal trends in weight and current weight‐related behaviour of Australian Aboriginal school‐aged children. Issue 11 (16th June 2014) - Hardy, Louise L; O'Hara, Blythe J; Hector, Debra; Engelen, Lina; Eades, Sandra J
Abstract: Objectives: To report 13‐year trends in weight status of Australian Aboriginal children, and to describe weight‐related behaviour in children in 2010, by Aboriginality. Design, setting and participants : Cross‐sectional population surveys of children aged 5–16 years ( n = 18 983) conducted in New South Wales schools in Term 1 of 1997, 2004 and 2010. Main outcome measures: For trend analysis: body mass index and waist‐to‐height ratio (WtHr). Analyses of weight‐related behaviour from 2010 survey data included indicators of dietary habits, screen time (ST) and physical activity. Results: Between 1997 and 2010, the relative increase in prevalence of overweight/obesity and WtHr ≥ 0.5 was 22.4% and 113.6%, respectively, among Aboriginal children, and 11.8% and 3.4%, respectively, among non‐Aboriginal children. In 2010, Aboriginal children had 1.52 (95% CI, 1.03–2.24) greater odds of having a WtHr ≥ 0.5 than non‐Aboriginal children. Compared with non‐Aboriginal children, Aboriginal children also had significantly lower odds of eating breakfast daily (adjusted odds ratio [AOR], 0.72; 95% CI, 0.52–0.99) and significantly greater odds of drinking ≥ 1 cup of soft drink daily (AOR, 1.61; 95% CI, 1.13–2.29), having a television in their bedroom (AOR, 2.75; 95% CI, 2.04–3.70), having no ST rules (AOR, 1.34; 95% CI, 1.04–1.73) and exceeding ST recommendations on weekdays (AOR, 1.78; 95% CI, 1.32–2.39). Conclusion s : Overweight/obesity and WtHr have increased more rapidly in Aboriginal than non‐Aboriginal children in NSW. Unhealthy weight‐related behaviour was frequent among all children, but lack of daily breakfast, excessive ST and soft drink consumption appear particularly problematic among Aboriginal children. Raising awareness with families of the consequences of excessive ST and encouraging strategies to limit ST (such as rethinking placement of televisions in children's bedrooms and implementing ST rules) hold promise.